2019
DOI: 10.3390/su11123265
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Remittances on Poverty in the Emerging Countries of the European Union

Abstract: In this paper we study the evolution of remittances and risk of poverty threshold for nine emerging countries in the European Union and analyzed the evolution and trend of the share of remittances in the risk of poverty threshold. The analysis was performed on data taken from the Eurostat database for the period 2005–2017. The statistical analysis of the data showed that the evolution of both remittances and risk of poverty threshold was heavily influenced by the global economic crisis. Although after the cris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The liberalization of capital movements and people worldwide, especially in Europe, have generated the reconfiguration of international financial flows. In addition, these phenomena have caused numerous economic, social, and political effects, both in the countries of origin and in the host countries (Gheasi and Nijkamp 2017;Mehedintu et al 2019). FDI has long been considered a universal panacea that would solve all problems related to the economic development of host countries.…”
Section: Introductionmentioning
confidence: 99%
“…The liberalization of capital movements and people worldwide, especially in Europe, have generated the reconfiguration of international financial flows. In addition, these phenomena have caused numerous economic, social, and political effects, both in the countries of origin and in the host countries (Gheasi and Nijkamp 2017;Mehedintu et al 2019). FDI has long been considered a universal panacea that would solve all problems related to the economic development of host countries.…”
Section: Introductionmentioning
confidence: 99%
“…Advancement in achieving this objective may be what policymakers, especially in developing countries, have so desperately needed in recent decades to achieve by fostering economic growth, implementing reform policies, or combining both. However, the poverty rates have varied considerably across countries, depending on the actual success of their economic growth, which leads to sustainable development [1][2][3][4]. The efforts of international institutions and public authorities on sustainable development can also support the process of reducing poverty and increasing the wellbeing of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, international development agencies and governments are considering the potential of employment and remittances to stimulate development in developing countries. In this regard, in a series of previous research on the emerging countries of the European Union [8][9][10], we studied the impact of remittances on economic growth and on poverty; we found that in the short term, the share of remittances in gross domestic product will maintain its upward trend for most of the countries analyzed, but the impact of the COVID-19 pandemic is unknown.…”
Section: Introductionmentioning
confidence: 99%